Kombinasi Media dan Pupuk untuk Produksi Padi dalam Sistem Budidaya Akuaponik di Bengkel Mimpi Malang - Cucun Herlina; Syaifullah Syaifullah; Aulia Rahmawati; Muhammad Dailami; Mohamad Fadjar; Ellana Sanoesi; Heny Suprastiyani; Rizky Fadilla Agustin Rangkuti; Wahyu Endra Kusuma; Abd. Rahem Faqih (PRIMA: Journal of Community Empowering and Services, 2026)
Combination of Growing Media and Fertilizers for Rice Production in the Aquaponic Farming System at Bengkel Mimpi Malang. Dependence on chemical fertilizers and limited home-garden space drive the search for efficient food production models. The aquaponic rice–catfish system is proposed as a solution to address land constraints, climate variability, and reliance on chemical fertilizers. This initiative aims to implement a smart farming model based on aquaponic principles to maintain household food security, enhance water-use efficiency, and reduce chemical input usage. The program will be conducted from May to September 2025 at Bengkel Mimpi (Kepanjen, Malang) through outreach, training, system installation, and mentoring. The system utilizes PVC pipes (plant spacing 25×25 cm) with wick-fed net pots placed above a tarpaulin-lined pond containing 3,000–5,000 catfish fingerlings. Two media formulations are tested: rice husk:manure (1:1) and rice husk charcoal:organic powder (1:3). The IR64 rice variety is harvested 80–90 days after planting, with 10–12 tillers per clump and 150–200 grains per panicle. One installation unit (2×12 m) yields approximately 30 kg of dry harvested paddy (≈20 kg of organic rice), with seven units producing approximately 210 kg/cycle, and a potential of 840 kg/year (four cycle). In the fish compartment, survival rates of 85-90% from an initial stocking of 5,000 fish yield approximately 500 kg of catfish/cycle, resulting in a net profit of about IDR 4.3 million/cycle. Media with higher organic proportions tend to increase tiller count and grain set. These findings confirm that the aquaponic system, when integrated, is a viable solution for household food security and income diversification, with measurable performance, making it suitable for widespread adoption in limited land environments.